DISKON, CITRA MEREK, DAN LAYANAN PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN DI MATAHARI DEPARTEMENT STORE DI KOTA JAMBI - Sucyani, Rachmadhanty (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This study examines discounts, brand image, and customer service simultaneously and partially to the purchase decision at Matahari Department Store Jambi City. The population used in this research is the people who shop any item at Matahari Department Store Jambi City, consisting of 100 respondents. While the analysis method used was multiple linear regression analysis. Simultaneous test results show that discount variables, brand image, and customer service significantly influence the purchase decision at Matahari Department Store Jambi City. Partial test results show discount variables, brand image, and customer service - each has a significant and positive influence on purchasing decisions in Matahari Department Store Kota Jambi. This condition is indicated by the considerable level of each variable below a = 5%.